2021
DOI: 10.3390/ijms22168454
|View full text |Cite
|
Sign up to set email alerts
|

NGS Analysis Confirms Common TP53 and RB1 Mutations, and Suggests MYC Amplification in Ocular Adnexal Sebaceous Carcinomas

Abstract: Ocular adnexal (OA) sebaceous carcinomas generally demonstrate more aggressive clinical and histopathological phenotypes than extraocular cases, but the molecular drivers implicated in their oncogenesis remain poorly defined. A retrospective review of surgical and ocular pathology archives identified eleven primary resection specimens of OA sebaceous carcinomas with adequate tissue for molecular analysis; two extraocular cases were also examined. Next-generation sequencing was used to evaluate mutations and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Molecular drivers involved in PSC oncogenesis remain poorly investigated. Recently, alterations in tumor protein p53 ( TP53 ) and retinoblastoma protein 1 ( RB1 ) have been reported as the most common alterations, and it has been suggested that MYC may contribute to the oncogenesis of these tumors 18 . In addition, high‐risk HPV infection has been demonstrated in a subset of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular drivers involved in PSC oncogenesis remain poorly investigated. Recently, alterations in tumor protein p53 ( TP53 ) and retinoblastoma protein 1 ( RB1 ) have been reported as the most common alterations, and it has been suggested that MYC may contribute to the oncogenesis of these tumors 18 . In addition, high‐risk HPV infection has been demonstrated in a subset of cases.…”
Section: Resultsmentioning
confidence: 99%
“…5a-c) and phakomatous choristoma (shown in Fig. 5d-f), are also illuminated in this chapter [31][32][33][34][35][36]. The material is coordinated with the 5th edition WHO Classification of the Tumours of the Skin, particularly with regard to cutaneous melanocytic tumors.…”
Section: Tumors Of the Eyelid (Table 6)mentioning
confidence: 98%
“…The protooncogenic role of MYC in physiologic epithelial differentiation and pathologic development of carcinomas has been well-documented, and copy number gain of the c-MYC locus has been recently described in sebaceous carcinomas of the ocular adnexa. 5,15 While, to the authors’ knowledge, there are no reports of MYC expression in canine sebaceous or MGs, upregulation of MYC has been reported in canine prostatic and mammary neoplasms. 7,8…”
mentioning
confidence: 96%
“…14,15 Sebaceous adenomas are more common than either sebaceomas or sebaceous epitheliomas and can be associated with syndromic microsatellite instability or mutations in genes encoding DNA mismatch repair proteins in affected Muir Torre patients. [14][15][16] Immunohistochemistry is often used to differentiate sebaceous carcinomas from benign lesions of the eyelid and other epithelial malignancies including basal and squamous cell carcinomas. 1,16 Here, we describe the features of the rare canine MG carcinoma and compare these features to the adenoma, which occurs more commonly in both man and dog.…”
mentioning
confidence: 99%
See 1 more Smart Citation